1983
DOI: 10.1111/j.2042-7158.1983.tb04351.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aprotinin on the rectal delivery of insulin

Abstract: COMMUNICATIONSfragmentation pathways are shown in Fig. 2. The mass spectrum of the metabolic product, which is appreciably different from the parent compound (Ia), suggests that the product was Ib.With benzylpiperazine (Ic) the original substrate only could be recovered from the incubation mixture.No 'in-vitro' degradation of the piperazine ring could be demonstrated in the present study and it is of interest that ring degradation products were found only in the tissues of rats after their being given substitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1984
1984
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The use of additives, such as enzyme inhibitors (1)(2)(3)(4), membrane permeability enhancers (5,6), and tight junction modulators (7)(8)(9), is one of the major strategies used to improve intestinal drug absorption. Alternatively, microparticles have been reported to improve the intestinal absorption of insulin (7,10,11) and siRNAs (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…The use of additives, such as enzyme inhibitors (1)(2)(3)(4), membrane permeability enhancers (5,6), and tight junction modulators (7)(8)(9), is one of the major strategies used to improve intestinal drug absorption. Alternatively, microparticles have been reported to improve the intestinal absorption of insulin (7,10,11) and siRNAs (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…Protease inhibitors can also be able to enhance rectal peptide absorption (59), but data on the viabilityof such compounds are very scarce. Nonetheless, studies from our Center demonstrated that both absorption enhancement and enzyme inhibition are prerequisites for effective rectal delivery of labile peptide drugs like DEyE (55).…”
Section: Rectal Transportmentioning
confidence: 99%